Two-amino acids change in the nsp4 of SARS coronavirus abolishes viral replication - Sakai, Yusuke; Kawachi, Kengo; Terada, Yutaka; Omori, Hiroko; Matsuura, Yoshiharu; Kamitani, Wataru (Virology (New York, N.Y.), 2017)
Infection with coronavirus rearranges the host cell membrane to assemble a replication/transcription complex in which replication of the viral genome and transcription of viral mRNA occur. Although coexistence of nsp3 and nsp4 is known to cause membrane rearrangement, the mechanisms underlying the interaction of these two proteins remain unclear. We demonstrated that binding of nsp4 with nsp3 is essential for membrane rearrangement and identified amino acid residues in nsp4 responsible for the interaction with nsp3. In addition, we revealed that the nsp3-nsp4 interaction is not sufficient to induce membrane rearrangement, suggesting the participation of other factors such as host proteins. Finally, we showed that loss of the nsp3-nsp4 interaction eliminated viral replication by using an infectious cDNA clone and replicon system of SARS-CoV. These findings provide clues to the mechanism of the replication/transcription complex assembly of SARS-CoV and could reveal an antiviral target for the treatment of betacoronavirus infection. •H120 and F121 in the lumenal loop in nsp4 are essential for binding to nsp3.•H120&F121 substitutions in nsp4 cause defect in membrane rearrangement function.•Interaction with nsp3 through H120&F121 in nsp4 is crucial for viral propagation.